An Analysis Of Determinants Stunting Incidents In Toddlers At Mazo Puskesmas UPT, South Nias District - Waoziduhu Ndruru; Ermi Girsang; Sri Lestari Ramadhani Nasution; Liani Br Ginting (Jurnal Scientia, 2024)
The problem of stunting is a disturbance in the growth of a child's height or body length, where the height growth does not match with increasing age, which is also an abnormal condition of the body caused by more than one factor (multifactor). So this re-search discusses many things, including analyzing the influence of clean water access, latrine access, hand washing behavior with soap (CTPS), history of exclusive breastfeed-ing and MP-ASI on the growth and development of toddlers aged 24-59 months. This research used a cross sectional study design. The research was conducted in March-April 2020. Respondents were 118 children under five (aged 24-59 months) who lived in Og-an Ilir. The selection of respondents was taken using a simple random sampling tech-nique. Stunting, a condition characterized by impaired growth and development in chil-dren due to poor nutrition, recurrent infections, and inadequate psychosocial stimulation, is a significant public health problem. Statistical analysis was carried out to identify cor-relations and potential causal relationships between these variables and the incidence of stunting. The results show that low socio-economic status and maternal education are significantly related to high stunting rates. Inadequate food intake and poor sanitation practices are also important factors. Frequent infections, especially gastrointestinal dis-eases, are known to worsen the risk of stunting in toddlers.The study concludes that a multifaceted approach is needed to address stunting, involving improved economic con-ditions, educational initiatives for mothers, improved nutrition programs, better access to health services, and improved sanitation facilities. These findings highlight the im-portance of integrated public health strategies to reduce stunting and improve the wel-fare of children in South Nias District. Further research is recommended to explore long-term interventions and their effectiveness in various settings.